Short-pulse laser-driven x-ray radiography. (21st September 2016) - Brambrink, E.; Baton, S.; Koenig, M.; Yurchak, R.; Bidaut, N.; Albertazzi, B.; Cross, J. E.; Gregori, G.; Rigby, A.; Falize, E.; Pelka, A.; Kroll, F.; et al.
Abstract : We have developed a new radiography setup with a short-pulse laser-driven x-ray source. Using a radiography axis perpendicular to both long- and short-pulse lasers allowed optimizing the incident angle of the short-pulse laser on the x-ray source target. The setup has been tested with various x-ray source target materials and different laser wavelengths. Signal to noise ratios are presented as well as achieved spatial resolutions. The high quality of our technique is illustrated on a plasma flow radiograph obtained during a laboratory astrophysics experiment on POLARs.